Growth, yield and root morphology of MR 220 and MR 263 rice (Oryza sativa) varieties under water stress and zinc fertilization - Inciong, Regine Stephanie Oliver (2016)
Growth and productivity of rice is adversely affected by water with numerous studies showing that water stress can significantly reduce final yield and quality of rice. In addition, micronutrient deficiency, specifically zinc affects millions of hectares of rice field in Asia alone. Since both water and zinc limit agricultural productivity and affect the potential yield of rice, a study was conducted in order to determine the effects of water and zinc application on plant growth, yield and root morphology of MR 220 and MR 263 rice varieties. The experiment was conducted at the University of Nottingham Malaysia Campus following a completely randomized design with three replications. Data was analyzed using GenStat program via Analysis of Variance (ANOVA) and Fisher’s Least Significant Difference (LSD) test at 5% level. Flowering was found to be the most sensitive growth stage to water stress since all of the growth parameters, as well as root traits (except for root length) were significantly affected by water. At maturity, most of the traits related to yield including grain weight were increased by daily watering. However, in terms of harvest index, results showed that 2-day interval watering was significantly higher. This suggests that 2-day interval watering scheme may be used in rice plants grown in the shade house without causing any large yield reduction. Moreover, the application of 25 kg/ha zinc did not have any significant effect in all the parameters as measured during the vegetative, flowering and maturity stages.